Pre-evaluation response of rhizosphere hybridization in acid lime - HOTA, DEBASHISH; KUMAR, VIJAY; SINGH, I P (The Indian Journal of Agricultural Sciences, 2021)
Rhizosphere hybridization is a new concept to secure the plant growth-promoting microorganisms to produce better nursery plants. Taking into the objective of rhizosphere hybridization, the present investigation was conducted in the secondary nursery block of ICAR-Central Citrus Research Institute, Nagpur. As many ten treatments consisting of rhizosphere microbes in form of water extract of the rhizosphere of acid lime, neem, bamboo, banyan and microbial consortium were tested in acid lime seedlings (cv NRCC Acid lime-7) raised on a solarized but containerized soil completely randomized design with three replications during 2018-20. Results showed a significant response to different treatments on plant growth parameters. In our study, the effect of the combined rhizosphere of banyan (Ficus benghalensis), neem (Azadirachta indica) and bamboo (Dendrocalamus strictus) was significantly superior to the rest of the treatments in increasing the biometric (seedling height, seedling diameter and number of branches per seedling), number of leaves per seedling, root architecture (tap root length, tap root diameter and number of secondary roots per seedling) and microbial biomass (fungal count and bacterial count) response of acid lime seedling compared to control treatment. Rhizosphere soil treatment was found to be superior over rhizosphere water extract treatment. Among various rhizosphere water extract treatments, acid lime rhizosphere water extract performed better in biometric response of acid lime seedling. Microbial consortium was observed to be better in increasing the microbial biomass of the rhizosphere, which could probably translate its response at later stages but added an additional resilience to rhizosphere, thereby, potentially effective in reducing the mortality once planted in main field.